Identifying strategies and techniques for the Egyptian medium and large size contractors to respond to economic hardship - Salib, Michael (AUC Knowledge Fountain, 2018)
There are numerous challenges and problems facing the construction industry in Egypt as a result of several economic influences and sovereign decisions, which are listed below: 1) The Central Bank of Egypt (CBE) increased the value of the US dollar against the Egyptian pound in the official market to reach USD/EGP 8.85 in March 14th, 2016. 2) Egypt’s parliament approved the value added tax (VAT) in September 8th, 2016. 3) The Egyptian Pound exchange rate liberalization in: November 3rd, 2016. 4) Hike in the value of projects' funding since November 3rd, 2016. 5) Fuel prices increased following the Central Bank of Egypt's decision to float the Egyptian Pound in November 4th, 2016. Many construction companies have shut down and left the market since 2016. The closure of these companies happened, as they did not acquire the experience and the managerial skills to deal with the economic hardship. They did not respond with the suitable techniques and strategies that will enable them to survive during this period of instability. This research identifies adequate strategies and techniques to be implemented by the first category contractors registered in the Egyptian Federation for Construction and Building Contractors that could enable them to survive during such economic conditions. The identification process is processed through two different methods. First, companies in other countries that have passed by similar conditions have been analyzed in order to identify the strategies and techniques they have used in order to survive. Second, interviews with experts in the Egyptian market have been conducted in order to identify the strategies implemented by their companies as a response to such economic instability. Furthermore, the strategies previously identified and applied in foreign markets are presented to those experts in order to study their applicability and efficiency if used in Egypt. A framework was developed in order to assist the construction companies in choosing the suitable techniques to their company size, through identifying the top ranked strategies and techniques that should be adopted by the company based on the parameters given to the framework. This framework has been verified by studying the financial statements of two companies, the first one has implemented almost all the top ranked strategies, and the other one has implemented only few strategies and techniques from the top tanked strategies. The figures concerning 2017 have been analyzed in respect to 2016, in order to visualize the effects of the strategies on the companies' financials. The framework has been also validated through experts' interviews. These experts have used and tested the framework and have rated through an interview its applicability and effectiveness. Furthermore, the experts have given few comments and recommendations in order to enhance the framework.